2022
DOI: 10.3390/coatings12030318
|View full text |Cite
|
Sign up to set email alerts
|

Facile In Situ Growth of Zif-8 Nanosheets with Enhanced Anti-Corrosion Performance for Carbon Steel in Seawater

Abstract: Carbon steel is one of the most important and widely used structural materials, but preventing its corrosion remains a great challenge. Herein, a metal–organic framework film consisting of Zif-8 nanosheets array was prepared using a one-step in situ growth method. This coating film can effectively inhibit the corrosion behavior of low carbon steel in seawater, resulting in improved corrosion resistance (4010 Ω·cm−2) and low corrosion current density (23 μA·cm−2). After long-term immersion in seawater, no notab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…20,21 In one research, ZIF8 nanosheet growth on the low-carbon steel diminished the corrosion rates of the steel substrate, and low corrosion current density was achieved. 22 Along with other methods that are applied to prevent metals' surfaces from corrosion, using organic coatings is a choice that is extensively focused on and is suggested that non-metallic layers like epoxy could be considered as a protective coating for reinforcing steel. Organic coatings like epoxy are extensively used in order to achieve high levels of protection for the metal surface against a corrosive environment.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 In one research, ZIF8 nanosheet growth on the low-carbon steel diminished the corrosion rates of the steel substrate, and low corrosion current density was achieved. 22 Along with other methods that are applied to prevent metals' surfaces from corrosion, using organic coatings is a choice that is extensively focused on and is suggested that non-metallic layers like epoxy could be considered as a protective coating for reinforcing steel. Organic coatings like epoxy are extensively used in order to achieve high levels of protection for the metal surface against a corrosive environment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among the zeolites, zeolitic imidazolate framework-8 (ZIF8) is known as the material that has the most stability in aqueous solutions, flexible structure, good hydrophobic properties, as well as uniform microstructures and is used as an appropriate active filler for anti-corrosion coating applications. It has been shown in many types of research studies that the hydrophobicity property of materials can adequately improve the adhesion and also stability of the coatings in the corrosive media. ZIF8-containing coatings are applied on the aluminum alloy and mild steel in order to achieve corrosion resistance improvement, and the electrochemical impedance spectroscopy results have proved a significant improvement in the corrosion resistance. , In one research, ZIF8 nanosheet growth on the low-carbon steel diminished the corrosion rates of the steel substrate, and low corrosion current density was achieved . Along with other methods that are applied to prevent metals’ surfaces from corrosion, using organic coatings is a choice that is extensively focused on and is suggested that non-metallic layers like epoxy could be considered as a protective coating for reinforcing steel.…”
Section: Introductionmentioning
confidence: 99%